Between China and Japan The Writings of Joshua Fogel - Fogel, Joshua A. 1950- (Brill, 2015)
These essays and reviews by Joshua Fogel, written over the past 35 years, focus on the cultural and political interactions between China and Japan. The represent pioneering efforts to assess these two histories together
Keywords: Geschichte; International relations; Internationale Politik; China / Relations / Japan; Japan / Relations / China; China; Japan; Aufsatzsammlung